2013
DOI: 10.1038/nchembio.1202
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-resolution monitoring of protein maturation in live human cells by NMR

Abstract: We used NMR directly in live human cells to describe the complete post-translational maturation process of human superoxide dismutase 1 (SOD1). We could follow, at atomic resolution, zinc binding, homodimer formation and copper uptake, and discover that copper chaperone for SOD1 (CCS) oxidation of the SOD1 intrasubunit disulfide bond occurs through both copper-dependent and independent mechanisms. Our approach represents a new strategy for structural investigation of endogeneously expressed proteins within a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
277
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(300 citation statements)
references
References 26 publications
19
277
0
4
Order By: Relevance
“…inside living cells. 'In-cell' and 'in-lysate' NMR spectroscopy (Danielsson et al 2013(Danielsson et al , 2015Serber et al 2005Serber et al , 2007Smith et al 2013) have developed to a point where new aspects of protein function can be revealed (Banci et al 2013). For instance in a recent study Selenko and co-workers developed an NMR-based methodology that enables quantification of the temporal phosphorylation and de-phosphorylation of short protein segments in cell lysates (Thongwichian et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…inside living cells. 'In-cell' and 'in-lysate' NMR spectroscopy (Danielsson et al 2013(Danielsson et al , 2015Serber et al 2005Serber et al , 2007Smith et al 2013) have developed to a point where new aspects of protein function can be revealed (Banci et al 2013). For instance in a recent study Selenko and co-workers developed an NMR-based methodology that enables quantification of the temporal phosphorylation and de-phosphorylation of short protein segments in cell lysates (Thongwichian et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…3), as observed for WT SOD1 (ref. 10). Chemical shift analysis shows that for the latter mutants only minor changes occur in the twodimensional (2D) NMR spectra, indicating that the overall structure is maintained in the E,Zn-SOD1 form, as the mutations only cause small local perturbations on the protein conformation ( Supplementary Fig.…”
Section: Impaired Zinc Binding Causes Accumulation Of Mutant Apo-sod1mentioning
confidence: 99%
“…10). With this approach, proteins are overexpressed and isotopically labelled in cultured human cells, and information on the intracellular folding, cysteine oxidation and metallation state of the protein is obtained by observing them directly in living cells by NMR.…”
mentioning
confidence: 99%
See 2 more Smart Citations